2014
DOI: 10.1186/1756-0500-7-688
|View full text |Cite
|
Sign up to set email alerts
|

Creatine kinase elevation caused by a combination of fluvastatin and telmisartan in a patient heterozygous for the CYP2C9*3 and ABCC2 -24C > T variants: a case report

Abstract: BackgroundGenetic factors as predictor of the individual outcome of drug therapy is one aim of personalized medicine approaches.Case presentationWe report a drug metabolism based analysis of genetic polymorphisms in a Caucasian patient receiving fluvastatin and telmisartan experiencing myotoxicity (myalgia and moderate creatine kinase elevation).ConclusionsThe obtained findings suggest that heterocygocity of cytochrome P450 CYP2C9*3 variant in combination with multidrug resistance-associated protein MRP2 -24C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Carriers of the TC genotype of SLCO1B1 rs4149056 (T>C) variant who are treated with amlodipine (CYP3A4 inhibitor) experienced a 90% increased simvastatin AUC compared with subjects not treated with amlodipine and wild-type for rs4149056 [87]. A similar scenario was reported with other two case reports (see Supplementary Table 1) [88,89].…”
Section: Ddgis and Challenges In Clinical Practicesupporting
confidence: 81%
“…Carriers of the TC genotype of SLCO1B1 rs4149056 (T>C) variant who are treated with amlodipine (CYP3A4 inhibitor) experienced a 90% increased simvastatin AUC compared with subjects not treated with amlodipine and wild-type for rs4149056 [87]. A similar scenario was reported with other two case reports (see Supplementary Table 1) [88,89].…”
Section: Ddgis and Challenges In Clinical Practicesupporting
confidence: 81%
“…Another study showed that the CYP2C9 polymorphism was related to the risk for fluvastatin-induced adverse drug reactions (ADRs). 12) In addition, this study also found an increased risk of ADRs when carriers of CYP2C9 variant alleles were given CYP2C9 inhibiting medicines concomitantly. A subsequent case report found that an elevation of the muscle tissue biomarker creatine kinase in a Caucasian patient genotyped as CYP2C9*1/*3 appeared to be caused by a DDI between fluvastatin and telmisartan, and a normalization was noticed after switching from telmisartan to candesartan.…”
mentioning
confidence: 53%
“…8) cines concomitantly. 12) Ohno et al 7) and Hisaka et al 8) have reported that careful attention needs to be paid to the co-administration of CYP3A4 inhibitors when using statins that are mainly metabolized by CYP3A4. It has also been reported that fluvastatin should be considered to be a good choice for patients who need to be treated by CYP3A4 inhibitors such as calcineurin inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Co-administration of FLU with telmisartan for several years resulted in mild myotoxicity as well as exhibited significant spinal motor neuron loss in vitro at lower concentrations as compared to other statins. [37,38] Incidence of hepatotoxicity was observed more frequently with FLU than the other statins [39] . These toxicities act as preliminary signals and future evaluations are certainly needed to confirm them and quantify these possible risks.…”
Section: In Silico Toxicity Predictionmentioning
confidence: 98%
“…The present in silico toxicity studies indicate carcinogenicity toxicity profile for rat male FDA none vs carcinogen toxicity model (Table S1) that might answer the increased incidence of thyroid follicular cells adenomas and carcinomas in males . Co‐administration of FLU with telmisartan for several years resulted in mild myotoxicity as well as exhibited significant spinal motor neuron loss in vitro at lower concentrations as compared to other statins . Incidence of hepatotoxicity was observed more frequently with FLU than the other statins .…”
Section: M1 and M2 ([M + H] + M/z 508) (Sulphation Of Hydroxylated Flu)mentioning
confidence: 99%